2007
DOI: 10.1093/ecam/nem045
|View full text |Cite
|
Sign up to set email alerts
|

Patient Disclosure about Herb and Supplement Use among Adults in the US

Abstract: Analyses of 2002 National Health Interview supplement on complementary and alternative medicine (NHI%AM) indicate that approximately 38 million adults in the US (18.9% of the population) used natural herbs or supplements in the preceding 12 months, but only one-third told their physician about this use. The objectives of this study are: (i) to determine subpopulation rates of patient–physician communication about herbal product and natural supplement use and (ii) to identify the relative influence of patient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 56 publications
4
61
0
1
Order By: Relevance
“…10 Despite the use of CAM by health care workers, nearly two-thirds of the users have reported not discussing their use of CAM with their physicians. 5,11 More recent studies 12 have indicated variable change in those disclosure rates; for instance, in cross-sectional surveys of pregnant women, disclosure rates of CAM use increased from less than 1% in 2006 to 50% in 2013. Disclosure rates in the United Kingdom are 20% to 40%.…”
Section: Background and Significance Of Cammentioning
confidence: 99%
“…10 Despite the use of CAM by health care workers, nearly two-thirds of the users have reported not discussing their use of CAM with their physicians. 5,11 More recent studies 12 have indicated variable change in those disclosure rates; for instance, in cross-sectional surveys of pregnant women, disclosure rates of CAM use increased from less than 1% in 2006 to 50% in 2013. Disclosure rates in the United Kingdom are 20% to 40%.…”
Section: Background and Significance Of Cammentioning
confidence: 99%
“…The concomitant intake of "supra-nutritional" flavonoid doses together with conventional drugs may lead to flavonoid-drug interactions [8]. Approximately 38 million adults in the US (18.9% of the population) use herbal products that contain flavonoids or other natural supplements, but only one third tell their physician about this use [9]. This lack of information, combined with the fact that natural products are usually a mixture of many active ingredients, increases the likelihood of harm.…”
Section: Introductionmentioning
confidence: 99%
“…Given these concordant views, it is surprising that the majority of patients do not disclose their supplement use to their providers. [35][36][37][38] Both parties are to blame-providers frequently do not ask about patients' supplement use, 35,39 and patients may not think to let their providers know. 40 Although providers may have inadequate information or suboptimal training regarding supplements, 41,42 in their interviews they much more frequently cited the importance of discussing certain topics than did patients.…”
Section: Discussionmentioning
confidence: 99%